The proto-oncogene LRF is under post-transcriptional control of MiR-20a: implications for senescence. - Laura Poliseno (PLoS ONE, 2008)
MicroRNAs (miRNAs) are short 20-22 nucleotide RNA molecules that act as negative regulators of gene expression via translational repression: they have been shown to play a role in development, proliferation, stress response, and apoptosis. The transcriptional regulator LRF (Leukemia/lymphoma Related Factor) has been shown to prevent p19ARF transcription and consequently to inhibit senescence in mouse embryonic fibroblasts (MEF). Here we report, for the first time, that LRF is post-transcriptionally regulated by miR-20a. Using a gene reporter assay, direct interaction of miR-20a with the LRF 3'UTR is demonstrated. To validate the interaction miR-20a/3'UTR LRF miR-20a was over-expressed, either by transient transfection or retroviral infection, in wild type mouse embryo fibroblasts and in LRF-null MEF derived from LRF knock-out mice. We observed LRF decrease, p19ARF increase, inhibition of cell proliferation and induction of senescence. The comparison of miR-20a activity in wt and LRF-null MEF indicates that LRF is the main mediator of the miR-20a-induced senescence and that other targets are cooperating. As LRF down-regulation/p19ARF induction is always accompanied by E2F1 down-regulation and increase of p16, we propose that all these events act in synergy to accomplish miR-20a-induced senescence in MEF. Senescence has been recently revaluated as a tumor suppressor mechanism, alternative to apoptosis; from this point of view the discovery of new physiological "senescence inducer" appears to be promising as this molecule could be used as anticancer drug.